Reducing Hysteresis Losses by Heating Minor Loops in Magnetocaloric Ni–Mn–Ga–Co Films - Diestel, Anett; Niemann, Robert; Schleicher, Benjamin; Nielsch, Kornelius; Faehler, Sebastian (Energy Technology, 2018)
Magnetocaloric materials relying on first-order phase transitions give the highest entropy changes compared to second-order transitions. However, they have the drawback of a transformation hysteresis, which reduces the efficiency of a cooling cycle. Here an approach to reduce the thermal hysteresis losses by performing incomplete transformation cycles, so called minor loops, is presented. A freestanding, epitaxially grown Ni–Mn–Ga–Co film is used as a model system to analyze the direct martensitic and reverse transformation paths in detail. The additional residual phase fraction only facilitates the forward martensitic transformation, but not the reverse transformation. This pronounced asymmetry between cooling and heating demonstrates that the forward transformation to martensite is controlled by nucleation and the associated excess energy contributes to hysteresis losses. For the reverse transformation, however, nuclei of austenite are always present and accordingly this transformation is controlled by growth of the austenitic phase. The experiments reveal that only the use of heating minor loops is useful to improve the efficiency of magnetocaloric epitaxial films and by this, the ratio of usable magnetization difference divided by hysteresis loss can be increased by 64 %.
CRIS-Team Scopus Importer:2022-04-14
Keywords: epitaxial films; magnetocaloric effects; martensitic transformations; minor loops; thermal hysteresis